A high impact polypropylene material and a method for its production

CN122941093APending Publication Date: 2026-10-20QINGDAO ZHONGBAO PLASTIC IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611113022.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-25
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

无论是无机粒子的填充效果,还是橡胶弹性体的分散结构,本质上均属于物理共混或亚微观尺度的界面结合,增韧剂与聚丙烯基体之间并未实现真正意义上的分子级融合与化学键合,以致于对聚丙烯的韧性效果不佳

Benefits of technology

1、由于本申请采用β晶成核剂和聚己内酯改性玉米芯纳米纤维,β晶对聚丙烯基体进行晶型转换,提升聚丙烯基体的韧性,聚己内酯改性玉米芯纤维作为增强体,利用天然纤维的刚性提升材料的模量和强度,且通过聚己内酯柔性层的桥梁作用,优化纳米纤维和聚丙烯基体的界面,既能传递应力,又能耗散能量,避免了界面缺陷,在增韧剂、玻璃纤维的协同作用下,使聚丙烯材料在受到冲击时,具有更好的抗冲击能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This application relates to the field of polymer materials, specifically disclosing a high-impact polypropylene material and its preparation method. The high-impact polypropylene material comprises the following raw materials in parts by weight: 80-100 parts polypropylene resin, 3-5 parts polycaprolactone-modified corn cob nanofibers, 3-8 parts β-crystal nucleating agent, 1-2 parts toughening agent, 0.1-1 part lubricant, 0.1-0.5 parts antioxidant, 5-15 parts nano-inorganic filler, and 5-10 parts glass fiber. The polypropylene material of this application incorporates polycaprolactone-modified corn cob nanofibers and a β-crystal nucleating agent, achieving impact modification of the polypropylene, resulting in not only excellent impact resistance but also outstanding low-temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polymer materials technology, and more specifically, to a high-impact polypropylene material and its preparation method. Background Technology

[0002] Polypropylene, a commonly used plastic material, possesses advantages such as excellent heat resistance, strong chemical corrosion resistance, high mechanical strength, good electrical insulation, and readily available molding properties, making it widely used in the automotive industry, home appliances, medical devices, and everyday consumer goods. However, traditional polypropylene materials suffer from poor low-temperature resistance and insufficient impact resistance, making them prone to brittle fracture in low-temperature environments or under external impact. This significantly limits its application in fields requiring higher performance.

[0003] To improve the toughness and impact resistance of polypropylene, the industry commonly uses toughening agents for modification. The toughening agents used are mainly classified into three categories: inorganic nanoparticles, inorganic rigid particles, and rubber or elastomers. The toughening mechanism of inorganic nanoparticles (such as nano-calcium carbonate and ultrafine silica) and inorganic rigid particles mainly utilizes the filling effect. By controlling the particle size of the filler particles and the interfacial bonding force between them and the polypropylene matrix, the toughness and strength of the material are improved. Rubber-based toughening agents (such as EPDM rubber and polyolefin elastomers) are usually dispersed in the polypropylene matrix in the form of elastic microdomains, improving the toughness and impact strength of the material by initiating and terminating crazes and absorbing impact energy.

[0004] Although the aforementioned toughening methods have improved the toughness of polypropylene to some extent, they still have significant limitations. Whether it's the filling effect of inorganic particles or the dispersion structure of the rubber elastomer, both are essentially physical blending or submicroscopic interfacial bonding. The toughening agent and the polypropylene matrix do not achieve true molecular-level fusion and chemical bonding, resulting in poor performance in improving the toughness of polypropylene. Summary of the Invention

[0005] In order to achieve a truly effective integration of the toughening component with the polypropylene matrix and overcome the problems of incompatibility and easy phase separation caused by physical blending of traditional toughening agents, thereby significantly and stably improving the low-temperature resistance and impact resistance of polypropylene materials, this application provides a high-impact polypropylene material and its preparation method.

[0006] In a first aspect, this application provides a high-impact polypropylene material, employing the following technical solution: A high-impact polypropylene material, comprising the following raw materials in parts by weight: 80-100 parts polypropylene resin, 3-5 parts polycaprolactone-modified corn cob nanofibers, 3-8 parts β-crystal nucleating agent, 1-2 parts toughening agent, 0.1-1 part lubricant, 0.1-0.5 parts antioxidant, 5-15 parts nano-inorganic filler, and 5-10 parts glass fiber.

[0007] By adopting the above technical solution, adding a β-crystal nucleating agent to polypropylene materials can induce PP to transform from α-crystal to β-crystal. β-crystal polypropylene has a unique crystal structure and can absorb more energy when subjected to impact, thus significantly improving the toughness of the material. Polycaprolactone-modified corn cob nanofibers combine biomass fillers and polymer toughening. Corn cob nanofibers are highly polar and have poor compatibility with non-polar polypropylene. Direct mixing affects the material properties. However, by modifying them with polycaprolactone, flexible PCL long chains are grafted onto the surface of corn cob nanofibers through a chemical reaction. Since PCL has certain compatibility with the polypropylene matrix, an interface layer is formed through entanglement, thereby making the corn cob nanofibers uniformly dispersed in the polypropylene matrix. Moreover, PCL is a tough material. The PCL segments grafted onto the surface of corn cob nanofibers form a flexible buffer layer between the corn cob nanofibers and the polypropylene matrix. When the material is subjected to impact, the buffer layer can dissipate energy through deformation, effectively transferring stress from the flexible PP matrix to the high-strength nanofibers, thus achieving synergistic toughening.

[0008] Preferably, the method for preparing the polycaprolactone-modified corn cob nanofibers is as follows: Corn cob nanofibers were dispersed in a 3-5 wt% polyethylene glycol aqueous solution, mixed evenly, and then freeze-dried to obtain an aerogel. After repeated washing, drying, and pulverizing, a mixture was obtained. Polycaprolactone and the mixture were mixed at a mass ratio of 1-2:10, heated to 120-130℃, kept at that temperature for 3-4 hours, cooled, pulverized, and sieved to obtain polycaprolactone-modified corn cob nanofibers.

[0009] By employing the above technical solution, polyethylene glycol is used as a dispersant to improve the uniform dispersion of corn cob nanofibers. After freeze-drying, the resulting aerogel is washed to remove polyethylene glycol, reducing the initiation polymerization of caprolactone monomers by polyethylene glycol and thus preventing the consumption of polycaprolactone, which would otherwise prevent caprolactone from being grafted onto the corn cob nanofibers. The surface of corn cob nanofibers contains hydroxyl groups, which can initiate the ring-opening polymerization of caprolactone, allowing caprolactone to polymerize and grow on its surface, thereby generating polycaprolactone-grafted modified corn cob nanofibers. The ring-opening reaction of caprolactone grafts flexible short chains onto the corn cob nanofiber molecules, disrupting the hydrogen bonds formed between the hydroxyl groups on the surface of the corn cob nanofibers, enhancing the interfacial interaction between the polypropylene matrix, and improving the impact resistance of the polypropylene matrix.

[0010] Preferably, the aerogel undergoes the following pretreatment before drying: Immerse the aerogel in an epoxy resin emulsion containing 3-5 wt% sodium chloride, degas at -0.09 to 0.1 MPa for 20-30 minutes, remove the aerogel, cure it at 140-150℃ for 1.5-2 hours, and wash it.

[0011] By adopting the above technical solution, corn cob nanofibers, under the dispersion effect of polyethylene glycol, interlock to form a three-dimensional network. After freeze-drying, a nanofiber network with an open-pore structure is formed, providing channels for the penetration of epoxy resin emulsion. Then, the epoxy resin emulsion is impregnated under negative pressure. After curing, the epoxy resin still contains unreacted epoxy groups, hydroxyl groups, and other active functional groups. During the grafting process of caprolactone, these groups can undergo ring-opening polymerization with caprolactone. After washing, the sodium chloride present in the epoxy resin is removed, forming pores in the epoxy resin skeleton. Therefore, the epoxy resin does not completely and densely encapsulate the nanofibers, thus affecting the grafting of caprolactone on the nanofiber surface. Therefore, PCL can not only be grafted onto the epoxy resin network but also continue to be grafted onto the nanofiber surface, forming a more complex interpenetrating network structure. The porous structure formed by the epoxy resin can, when the material is subjected to impact, blunt the crack tip, absorb energy, and hinder crack propagation, thereby achieving a toughening effect.

[0012] Preferably, the β-crystal nucleating agent comprises ultra-high molecular weight polyethylene swelling body and zinc adipic acid in a mass ratio of 0.1-0.2:1.

[0013] By adopting the above technical solution, ultra-high molecular weight polyethylene (UHMWPE) has an extremely high molecular weight and highly entangled macromolecular chains, resulting in high melt viscosity, which affects the uniformity of dispersion. Moreover, when nucleating agents are added directly, it is difficult to avoid their agglomeration, making it impossible to achieve relatively uniform dispersion and reducing nucleation efficiency. Therefore, UHMWPE is first swollen to untangle its molecular chains and reduce its apparent viscosity. It is then mixed with zinc adipic acid. Zinc adipic acid uses the swollen UHMWPE as a dispersion carrier, and under the shearing action of the screw, it is more easily dispersed in the polypropylene matrix, achieving uniform dispersion, thereby exerting its nucleation effect and improving nucleation efficiency.

[0014] Preferably, the β-crystal nucleating agent is prepared by the following method: Ultra-high molecular weight polyethylene and white oil are mixed at a mass ratio of 1:0.5-1, swollen at 130-140℃ for 20-30 minutes, and cooled to 50-80℃ to obtain an ultra-high molecular weight polyethylene swollen body. Adipic acid was added to an ethanol / water mixture, zinc oxide was added, and the mixture was stirred until homogeneous. The mixture was then added to an ultra-high molecular weight polyethylene swellable body, stirred to react, and extracted with acetone to obtain a β-crystal nucleating agent.

[0015] By adopting the above technical solution, ultra-high molecular weight polyethylene (UHMWPE) is first swollen with white oil, causing the UHMWPE molecular chains to untangle and form a viscous swollen body. This provides an ideal, high-viscosity reaction medium for the subsequent reaction of adipic acid and zinc oxide. A mixed solution of ethanol / water is then used to penetrate adipic acid and zinc oxide into the oil phase network of the UHMWPE swollen body. Zinc oxide is dispersed into the pores of the oil phase network, while adipic acid and zinc oxide undergo acid-base neutralization, generating solid zinc adipic acid in situ. This solid zinc adipic acid is evenly distributed in the UHMWPE network skeleton and pores, improving the dispersibility of zinc adipic acid in the polypropylene matrix and enhancing its nucleation effect.

[0016] Preferably, the ultra-high molecular weight polyethylene swelling body also contains polyoxyethylene fatty acid ester, and the mass ratio of polyoxyethylene fatty acid ester to ultra-high molecular weight polyethylene is 0.01-0.05:1.

[0017] By adopting the above technical solution, polyoxyethylene fatty acid ester is a nonionic surfactant, which is prepared by the addition reaction of fatty acids and ethylene oxide. Its hydrophilic groups (polyoxyethylene chain) and hydrophobic groups (fatty acid chain) in its molecular structure give it excellent wetting, dispersing and solubilizing properties. Its hydrophobic end is entangled with the ultra-high molecular weight polyethylene molecular chain and white oil, while the hydrophilic end is combined with the surface of adipic acid or zinc oxide particles through hydrogen bonds, thereby stably distributing the hydrophilic component in the oil phase, improving the compatibility of hydrophobic ultra-high molecular weight polyethylene swelling body with adipic acid and zinc oxide, and making the in-situ synthesized zinc adipic acid uniformly fill the molecular network backbone of ultra-high molecular weight polyethylene.

[0018] Preferably, the toughening agent comprises thermoplastic styrene-butadiene rubber and ethylene-sodium acetate ethylene copolymer in a mass ratio of 1:0.5-1.

[0019] Preferably, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 168, and antioxidant 1076; The nano-inorganic filler is selected from at least one of nano-silica, nano-calcium carbonate and talc. The lubricant is selected from at least one of polyethylene wax, stearate and pentaerythritol stearate.

[0020] Secondly, this application provides a method for preparing a high-impact polypropylene material, employing the following technical solution: A method for preparing a high-impact polypropylene material includes the following steps: Polypropylene resin, polycaprolactone-modified corn cob nanofibers, β-crystal nucleating agent, toughening agent, glass fiber, antioxidant and nano-inorganic filler are mixed and stirred evenly to obtain a premix. High-impact polypropylene material is obtained by extruding and granulating the premixed material using a twin-screw extruder.

[0021] In summary, this application has the following beneficial effects: 1. Because this application uses β-crystal nucleating agent and polycaprolactone-modified corn cob nanofibers, β-crystals perform crystal transformation on the polypropylene matrix, improving the toughness of the polypropylene matrix. Polycaprolactone-modified corn cob fibers serve as reinforcements, utilizing the rigidity of natural fibers to improve the modulus and strength of the material. Furthermore, through the bridging effect of the polycaprolactone flexible layer, the interface between the nanofibers and the polypropylene matrix is ​​optimized, which can both transmit stress and dissipate energy, avoiding interface defects. With the synergistic effect of toughening agents and glass fibers, the polypropylene material has better impact resistance when subjected to impact.

[0022] 2. In this application, ultra-high molecular weight polyethylene (UHMWPE) swellable body and zinc adipic acid are preferred for preparing β-crystal nucleating agent. The UHMWPE after swelling is used as a dispersion medium, which can increase the dispersibility of zinc adipic acid in polypropylene matrix, so that the nucleating agent is better and more uniformly dispersed in polypropylene system. This avoids the problem of decreased nucleation efficiency caused by powder agglomeration, and ensures that a large number of uniform and fine β-crystal spherules can be formed in polypropylene matrix, so as to achieve stable and efficient toughening effect.

[0023] 3. In this application, epoxy resin and sodium chloride are preferably used in the preparation of polycaprolactone-modified corn cob nanofibers to construct a porous epoxy resin skeleton in the aerogel formed by the corn cob nanofibers. The porous structure combined with fiber reinforcement improves the toughness and strength of the polypropylene material. Detailed Implementation

[0024] The present application will be further described in detail below with reference to the embodiments.

[0025] Example of corn cob nanofiber preparation Preparation Example I: (1) Crush corn cobs, add water to make the moisture content reach 60%, mix and stir for 20 min, put them into a sealed bag, place for 24 h, and use a continuous screw flash explosion device for flash explosion treatment. The screw speed is 250 r / min, the temperature is 150℃, the pressure is 1.5 MPa, repeat 6 times, freeze dry, and obtain pretreated material; (2) The pretreated material was mixed with a 2wt% sodium hydroxide solution at a solid-liquid ratio of 20 and stirred at room temperature for 12 hours. The mixture was then washed repeatedly with deionized water until the pH was neutral. The mixture was then mixed with a 3wt% NaClO solution at a solid-liquid ratio of 1:10 and sodium hydroxide was added until the pH was 12. The mixture was stirred at room temperature for 6 hours and washed repeatedly with deionized water until the pH was neutral to obtain corn cob nanofibers.

[0026] Preparation Examples of Polycaprolactone-Modified Corn Cob Nanofibers 1-6 In the following preparation examples, caprolactone was selected from Dezhou Huazhen New Materials, model number HZ443, and epoxy resin E51 was selected from Changzhou Lebang Composite Materials, with a viscosity of 12000 mPas.

[0027] Preparation Example 1: 20g of corn cob nanofibers prepared in Preparation Example I were dispersed in a 5wt% polyethylene glycol aqueous solution to make the concentration of corn cob nanofibers 0.5wt%. Then, the dispersion was carried out at 48000rpm for 1min, ultrasonically treated with 1000W power for 30min, pre-frozen at -18℃ for 12h, and freeze-dried at -50℃ and vacuum degree 1Pa for 48h to obtain an aerogel. The aerogel was repeatedly washed with deionized water, dried at 80℃ to constant weight, and then pulverized to 5μm to obtain a mixture. Caprolactone and the mixture were mixed at a mass ratio of 2:10, stirred for 10 min, heated from room temperature to 130℃ at a rate of 10℃ / h, kept at that temperature for 3 h, cooled to room temperature, pulverized and passed through a 200-mesh sieve to obtain polycaprolactone-modified corn cob nanofibers.

[0028] Preparation Example 2: 20g of corn cob nanofibers prepared in Preparation Example I were dispersed in a 3wt% polyethylene glycol aqueous solution to make the concentration of corn cob nanofibers 0.5wt%. Then, the dispersion was carried out at 48000rpm for 1min, ultrasonically treated with 1000W power for 30min, pre-frozen at -18℃ for 12h, and freeze-dried at -50℃ and vacuum degree 1Pa for 48h to obtain an aerogel. The aerogel was repeatedly washed with deionized water, dried at 80℃ to constant weight, and then pulverized to 5μm to obtain a mixture. Caprolactone and the mixture were mixed at a mass ratio of 1:10, stirred for 10 min, heated from room temperature to 120℃ at a rate of 10℃ / h, kept at that temperature for 4 h, cooled to room temperature, pulverized and passed through a 200-mesh sieve to obtain polycaprolactone-modified corn cob nanofibers.

[0029] Preparation Example 3: The difference from Preparation Example 1 is that the aerogel was not repeatedly washed. Instead, the aerogel was dried at 80°C to constant weight and then pulverized to 5 μm to obtain a mixture.

[0030] Preparation Example 4: The difference from Preparation Example 1 is that the aerogel underwent the following pretreatment before drying: 10g of epoxy resin E51 was diluted to a concentration of 5wt%. 8g of curing agent cis-hexahydrophthalic anhydride, heated to liquid state at 70℃, was added. Then, 0.03g of accelerator 2,4,6-tris(dimethylaminotoluene)phenol and 0.05g of defoamer silicone oil were added. The mixture was stirred for 10 minutes to obtain an epoxy resin emulsion. 10g of sodium chloride was added, and the mixture was defoamed in a vacuum oven at 60℃ for 30 minutes to obtain an epoxy resin emulsion containing sodium chloride. The aerogel was immersed in an epoxy resin emulsion containing sodium chloride, degassed at -0.09 MPa for 30 min, removed, cured at 140℃ for 2 h, and repeatedly washed with water to remove sodium chloride.

[0031] Preparation Example 5: The difference from Preparation Example 1 is that the aerogel underwent the following pretreatment before drying: 10g of epoxy resin E51 was diluted to a concentration of 3wt%. 8g of curing agent cis-hexahydrophthalic anhydride, heated to liquid state at 70℃, was added. Then, 0.03g of accelerator 2,4,6-tris(dimethylaminotoluene)phenol and 0.05g of defoamer silicone oil were added. The mixture was stirred for 10 minutes to obtain an epoxy resin emulsion. 5g of sodium chloride was added, and then the mixture was degassed in a vacuum oven at 60℃ for 30 minutes to obtain an epoxy resin emulsion containing sodium chloride. The aerogel was immersed in an epoxy resin emulsion containing sodium chloride, degassed at -0.1 MPa for 20 min, removed, cured at 150℃ for 1.5 h, and repeatedly washed with water to remove sodium chloride.

[0032] Preparation Example 6: The difference from Preparation Example 4 is that sodium chloride was not added to the epoxy resin emulsion.

[0033] Example In the following examples, syndiotactic polypropylene was selected from BASF, model 1100LX; thermoplastic styrene-butadiene rubber was selected from Baling Petrochemical, grade YH-792E; ethylene-sodium acetate ethylene copolymer was selected from Taiwan Plastics, model 7470M; ultra-high molecular weight polyethylene was selected from Ticona, model GUR4120; white oil was selected from Suzhou Hesen, 15# white oil, flash point 164-223℃; and polyoxyethylene fatty acid ester was selected from Sanda Chemical, model A-103.

[0034] Example 1: A high-impact polypropylene material comprising the following raw materials by weight: 100g polypropylene resin, 5g polycaprolactone-modified corn cob nanofibers, 5g β-crystal nucleating agent, 2g toughening agent, 0.5g lubricant, 0.3g antioxidant, 15g nano-inorganic filler, and 10g glass fiber. The polypropylene resin is syndiotactic polypropylene, the polycaprolactone-modified corn cob nanofibers are prepared according to Preparation Example 1, the β-crystal nucleating agent is zinc adipate, the toughening agent is prepared by mixing thermoplastic styrene-butadiene rubber and ethylene-sodium acetate copolymer in Preparation Example 1:1, the lubricant is polyethylene wax, the antioxidant is a compound formed by antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio, the nano-inorganic filler is nano-silica, and the glass fiber has a length of 4.5mm and a diameter of 11μm.

[0035] The preparation method of the above-mentioned high-impact polypropylene material includes the following steps: Polypropylene resin, polycaprolactone-modified corn cob nanofibers, β-crystal nucleating agent, toughening agent, glass fiber, antioxidant and nano-inorganic filler are mixed and stirred evenly to obtain a premix. The premixed material is extruded and granulated by a twin-screw extruder to obtain high-impact polypropylene material. The screw temperatures of the twin-screw extruder in the direction of material advance are: 80℃, 100℃, 130℃, 170℃, 180℃, 180℃, 180℃, 190℃, 190℃, 190℃, the main extruder speed is 80r / min, and the feeding speed is 8r / min.

[0036] Example 2: A high-impact polypropylene material, differing from Example 1 in the following raw material amounts: 90g polypropylene resin, 4g polycaprolactone-modified corn cob nanofibers, 8g β-crystal nucleating agent, 1.5g toughening agent, 1g lubricant, 0.5g antioxidant, 10g nano-inorganic filler, and 5g glass fiber. The polypropylene resin is syndiotactic polypropylene, the polycaprolactone-modified corn cob nanofibers are prepared in Example 2, the β-crystal nucleating agent is zinc adipate, the toughening agent is a mixture of thermoplastic styrene-butadiene rubber and ethylene-sodium acetate copolymer from Example 1:1, the lubricant is pentaerythritol stearate, the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio, the nano-inorganic filler is talc, and the glass fiber has a length of 4.5mm and a diameter of 11μm.

[0037] The preparation method of the high-impact polypropylene material in Example 2 is the same as that in Example 1.

[0038] Example 3: A high-impact polypropylene material, differing from Example 1 in the following raw material amounts: 80g polypropylene resin, 3g polycaprolactone-modified corn cob nanofibers, 3g β-crystal nucleating agent, 1g toughening agent, 0.5g lubricant, 0.1g antioxidant, 5g nano-inorganic filler, and 8g glass fiber. The polypropylene resin is syndiotactic polypropylene, the polycaprolactone-modified corn cob nanofibers are prepared according to Preparation Example 1, the β-crystal nucleating agent is zinc adipate, the toughening agent is a mixture of thermoplastic styrene-butadiene rubber and ethylene-sodium acetate copolymer from Preparation Example 1:1, the lubricant is calcium stearate, the antioxidant is a compound formed by antioxidant 1010 and antioxidant 1076 in a 1:1 mass ratio, the nano-inorganic filler is nano-calcium carbonate, and the glass fiber has a length of 4.5mm and a diameter of 11μm.

[0039] The preparation method of the high-impact polypropylene material in Example 3 is the same as that in Example 1.

[0040] Example 4: A high-impact polypropylene material, which differs from Example 1 in that the polycaprolactone-modified corn cob nanofibers are made from Preparation Example 3.

[0041] Example 5: A high-impact polypropylene material, which differs from Example 1 in that the polycaprolactone-modified corn cob nanofibers are made from Preparation Example 4.

[0042] Example 6: A high-impact polypropylene material, which differs from Example 1 in that the polycaprolactone-modified corn cob nanofibers are made from Preparation Example 5.

[0043] Example 7: A high-impact polypropylene material, which differs from Example 5 in that the polycaprolactone-modified corn cob nanofibers are made from Preparation Example 6.

[0044] Example 8: A high-impact polypropylene material, differing from Example 1 in that the β-crystal nucleating agent comprises ultra-high molecular weight polyethylene swellable body and zinc adipic acid in a mass ratio of 0.2:1, and the β-crystal nucleating agent is prepared by the following method: Ultra-high molecular weight polyethylene (UHMWPE) was added to white oil at a mass ratio of 1:1. The mixture was swollen at 130°C for 30 minutes and then cooled to obtain a UHMWPE swollen body. Zinc adipic acid is added to the swollen body of ultra-high molecular weight polyethylene and stirred until homogeneous.

[0045] Example 9: A high-impact polypropylene material, differing from Example 8 in that the β-crystal nucleating agent comprises ultra-high molecular weight polyethylene swellable body and zinc adipic acid in a mass ratio of 0.2:1, and the β-crystal nucleating agent is prepared by the following method: Ultra-high molecular weight polyethylene (UHMWPE) was added to white oil at a mass ratio of 1:1. The mixture was swollen at 130°C for 30 minutes and then cooled to obtain a UHMWPE swollen body. Add 3g of adipic acid to a 10ml mixture of ethanol / water (volume ratio 9:1), add 1.6g of zinc oxide, stir well, and then add to the swollen body of ultra-high molecular weight polyethylene. Stir and react, then extract with acetone to obtain the β-crystal nucleating agent.

[0046] Example 10: A high-impact polypropylene material, differing from Example 8 in that the β-crystal nucleating agent comprises ultra-high molecular weight polyethylene swellable body and zinc adipic acid in a mass ratio of 0.1:1, and the β-crystal nucleating agent is prepared by the following method: Ultra-high molecular weight polyethylene (UHMWPE) was added to white oil at a mass ratio of 0.5:1. The mixture was swollen at 130°C for 30 minutes and then cooled to obtain a UHMWPE swollen body. Add 3.17g of adipic acid to 10ml of ethanol / water (volume ratio 9:1), add 1.76g of zinc oxide, stir well, and then add to the swollen body of ultra-high molecular weight polyethylene. Stir the reaction and extract with acetone to obtain the β-crystal nucleating agent.

[0047] Example 11: A high-impact polypropylene material, differing from Example 8 in that the β-crystal nucleating agent comprises ultra-high molecular weight polyethylene swellable body and zinc adipic acid in a mass ratio of 0.2:1, and the β-crystal nucleating agent is prepared by the following method: Ultra-high molecular weight polyethylene (UHMWPE) was added to white oil, and polyoxyethylene fatty acid ester was added. The mass ratio of UHMWPE, white oil and polyoxyethylene fatty acid ester was 1:1:0.05. The mixture was swollen at 130°C for 30 min and then cooled to obtain a UHMWPE swollen body. Add 3g of adipic acid to a 10ml mixture of ethanol / water (volume ratio 9:1), add 1.6g of zinc oxide, stir well, and then add to the swollen body of ultra-high molecular weight polyethylene. Stir and react, then extract with acetone to obtain the β-crystal nucleating agent.

[0048] Example 12: A high-impact polypropylene material, differing from Example 1 in that the polycaprolactone-modified corn cob nanofibers are prepared according to Preparation Example 4, and the β-crystal nucleating agent contains ultra-high molecular weight polyethylene swellable body and zinc adipic acid in a mass ratio of 0.2:1. The β-crystal nucleating agent is prepared by the following method: ultra-high molecular weight polyethylene is added to white oil, and polyoxyethylene fatty acid ester is added. The mass ratio of ultra-high molecular weight polyethylene, white oil and polyoxyethylene fatty acid ester is 1:1:0.05. The mixture is swelled at 130°C for 30 min, cooled, and ultra-high molecular weight polyethylene swellable body is obtained. Add 3g of adipic acid to a 10ml mixture of ethanol / water (volume ratio 9:1), add 1.6g of zinc oxide, stir well, and then add to the swollen body of ultra-high molecular weight polyethylene. Stir and react, then extract with acetone to obtain the β-crystal nucleating agent.

[0049] Comparative Example Comparative Example 1: A high-impact polypropylene material, which differs from Example 1 in that the nucleating agent is α-crystal nucleating agent 1,3:2,4-bis(3,4-dimethylbenzyl)-D-sorbitol.

[0050] Comparative Example 2: A high-impact polypropylene material, which differs from Example 1 in that the corn cob nanofibers are not modified with polycaprolactone, and the corn cob nanofibers are made from Preparation Example I.

[0051] Performance testing The prepared polypropylene material was dried and then injection molded. The injection molding machine was set with the barrel temperature in the material forward direction as 150℃, 160℃, 170℃, and 170℃, and the injection pressure as 60MPa. The performance was tested according to the following method, and the test results were recorded in Table 1.

[0052] 1. Tensile strength: The test was conducted in accordance with GB / T1040.1-2018 "Determination of tensile properties of plastics - Part 1: General". The original gauge length was 30 mm, the strip width was 5 mm, the thickness was 2 mm, and the tensile rate was 5 mm / min. Five parallel samples were tested for each sample, and the average value was taken.

[0053] 2. Bending strength: The test was conducted in accordance with GB / T9341-2008 "Determination of bending properties of plastics". The support span was 86 mm, the sample thickness was 6 mm, the width was 15 mm, the descent rate was 5 mm / min, and 5 samples were tested for each sample. The average value was taken.

[0054] 3. Impact strength: The impact test was conducted in accordance with GB / T1043.1-2008 "Determination of impact properties of simply supported plastic beams - Part 1: Non-instrumental impact test". The pendulum was 15J, the span was 70mm, and the notch type was A. Five specimens were tested for each sample, and the average value was taken.

[0055] 4. Low temperature resistance test: At -20℃, the impact strength of the sample was tested according to GB / T1043.1-2008 "Determination of impact properties of simply supported plastic beams - Part 1: Non-instrumental impact test". The pendulum was 15J, the span was 70mm, and the notch type was A. Five samples were tested for each sample and the average value was taken.

[0056] Table 1 Performance test results of polypropylene materials

[0057] Based on the raw material usage in Examples 1-3 and the data in Table 1, it can be seen that by using polypropylene resin as the matrix and adding specific amounts of polycaprolactone-modified corn cob nanofibers, β-crystal nucleating agents, glass fibers, and inorganic fillers, a polypropylene material with good impact resistance and low-temperature performance can be obtained.

[0058] Compared with Example 1, Example 4 used polycaprolactone-modified corn cob nanofibers prepared in Preparation Example 3, in which the aerogel was not washed to remove polyethylene glycol. The data in Table 1 show that the tensile strength and other mechanical properties of the polypropylene material decreased, and the low-temperature resistance was weakened. This indicates that the presence of polyethylene glycol without washing caused the hydroxyl groups of the caprolactone to combine with the polyethylene glycol, resulting in insufficient grafting of polycaprolactone into the corn cob nanofibers. This led to a decrease in its dispersibility in the polypropylene matrix, affecting the mechanical properties of the polypropylene material.

[0059] In Examples 5 and 6, polycaprolactone-modified corn cob nanofibers prepared in Preparation Examples 4 and 5 were used, respectively. Compared with Preparation Example 1 in Example 1, the aerogel was filled with an epoxy resin emulsion containing sodium chloride. The data in Table 1 show that although the elongation at break of the polypropylene material prepared in this way decreased, the tensile strength and flexural strength were significantly enhanced, the impact strength was increased, and the low-temperature resistance was improved. This indicates that the filling of the porous epoxy resin skeleton can increase the toughness of the polypropylene material.

[0060] Compared with Example 5, Example 7 did not add sodium chloride to the epoxy resin emulsion. The polypropylene material prepared in Example 7 showed a decrease in impact strength and an increase in rigidity, indicating that the porous epoxy resin skeleton formed by adding sodium chloride can effectively improve the impact strength of polypropylene material and achieve a synergistic effect of combining rigidity and flexibility.

[0061] Compared with Example 1, Example 8 uses ultra-high molecular weight polyethylene (UHMWPE) swellable body and zinc adipic acid to prepare β-crystal nucleating agent. It can be seen that with UHMWPE swellable body as the dispersion medium, the nucleation efficiency of zinc adipic acid increases, and the tensile strength and impact strength of the polypropylene material produced increases.

[0062] Compared with Example 8, Examples 9 and 10 used adipic acid and zinc oxide to synthesize zinc adipic acid in situ within ultra-high molecular weight polyethylene (UHMWPE) swellable bodies. As shown in Table 1, the polypropylene materials prepared in Examples 9 and 10 exhibited higher tensile strength, impact strength, and other properties than those in Example 8. This indicates that in situ synthesis of zinc adipic acid within UHMWPE swellable bodies can better improve the mechanical strength of polypropylene materials.

[0063] Compared with Example 8, Example 11 added polyoxyethylene fatty acid ester when preparing the ultra-high molecular weight polyethylene swelling body. As can be seen from the data comparison in Table 1, the tensile strength, impact strength and other properties of the polypropylene material prepared in Example 11 were improved. This indicates that adding polyoxyethylene fatty acid ester can improve the dispersibility of zinc adipic acid in the ultra-high molecular weight polyethylene swelling body and improve the nucleation effect.

[0064] Compared with Example 1, Example 12 not only used the polycaprolactone-modified corn cob nanofibers prepared in Example 4, but also used ultra-high molecular weight polyethylene swelling body and zinc adipic acid to prepare β-crystal nucleating agent. Compared with Example 5 and Example 11, the tensile strength, flexural strength, impact strength and low temperature resistance of the polypropylene material were improved.

[0065] Compared with Example 1, Comparative Example 1 uses an α-crystal nucleating agent, resulting in a polypropylene material with decreased tensile strength, impact strength, and low-temperature resistance.

[0066] Compared with Example 1, Comparative Example 2 did not use polycaprolactone to modify corn nanofibers. As can be seen from the data in Table 1, the tensile strength and mechanical properties such as impact strength of the polypropylene material decreased significantly.

[0067] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A high-impact polypropylene material, characterized in that, Including the following parts by weight of raw materials: 80-100 parts polypropylene resin, 3-5 parts polycaprolactone-modified corn cob nanofibers, 3-8 parts β-crystal nucleating agent, 1-2 parts toughening agent, 0.1-1 part lubricant, 0.1-0.5 parts antioxidant, 5-15 parts nano-inorganic filler, and 5-10 parts glass fiber.

2. The high-impact polypropylene material according to claim 1, characterized in that: The method for preparing the polycaprolactone-modified corn cob nanofibers: Corn cob nanofibers were dispersed in a 3-5 wt% polyethylene glycol aqueous solution, mixed evenly, and then freeze-dried to obtain an aerogel. After repeated washing, drying, and pulverizing, a mixture was obtained. Polycaprolactone and the mixture were mixed at a mass ratio of 1-2:10, heated to 120-130℃, kept at that temperature for 3-4 hours, cooled, pulverized, and sieved to obtain polycaprolactone-modified corn cob nanofibers.

3. The high impact-resistant polypropylene material according to claim 2, characterized in that: Before the aerogel dries, the following pretreatment is performed: Immerse the aerogel in an epoxy resin emulsion containing 3-5 wt% sodium chloride, degas at -0.09 to 0.1 MPa for 20-30 minutes, remove the aerogel, cure it at 140-150℃ for 1.5-2 hours, and wash it.

4. The high-impact polypropylene material according to claim 1, characterized in that: The β-crystal nucleating agent comprises ultra-high molecular weight polyethylene swelling body and zinc adipic acid in a mass ratio of 0.1-0.2:

1.

5. The high-impact polypropylene material according to claim 4, characterized in that: The β-crystal nucleating agent is prepared by the following method: Ultra-high molecular weight polyethylene and white oil are mixed at a mass ratio of 1:0.5-1, swollen at 130-140℃ for 20-30 minutes, and cooled to 50-80℃ to obtain an ultra-high molecular weight polyethylene swollen body. Adipic acid was added to an ethanol / water mixture, zinc oxide was added, and the mixture was stirred until homogeneous. The mixture was then added to an ultra-high molecular weight polyethylene swellable body, stirred to react, and extracted with acetone to obtain a β-crystal nucleating agent.

6. The high-impact polypropylene material according to claim 5, characterized in that: The ultra-high molecular weight polyethylene swelling body also contains polyoxyethylene fatty acid ester, and the mass ratio of polyoxyethylene fatty acid ester to ultra-high molecular weight polyethylene is 0.01-0.05:

1.

7. The high-impact polypropylene material according to claim 1, characterized in that: The toughening agent comprises thermoplastic styrene-butadiene rubber and ethylene-sodium acetate ethylene copolymer in a mass ratio of 1:0.5-1.

8. The high-impact polypropylene material according to claim 1, characterized in that: The antioxidant is selected from at least one of antioxidant 1010, antioxidant 168, and antioxidant 1076; The nano-inorganic filler is selected from at least one of nano-silica, nano-calcium carbonate and talc. The lubricant is selected from at least one of polyethylene wax, stearate and pentaerythritol stearate.

9. A method for preparing the high-impact polypropylene material according to any one of claims 1-8, characterized in that, Includes the following steps: Polypropylene resin, polycaprolactone-modified corn cob nanofibers, β-crystal nucleating agent, toughening agent, glass fiber, antioxidant and nano-inorganic filler are mixed and stirred evenly to obtain a premix. High-impact polypropylene material is obtained by extruding and granulating the premixed material using a twin-screw extruder.